Performance of pre-bearing acid lime (Citrus aurantifolia) on various rootstock strains - RAM, LALLAN; SINGH, SHYAM; MARATHE, R A (The Indian Journal of Agricultural Sciences, 2013)
A study was conducted during 1994-96 on the pre-bearing perfonnance of acid lime (CitruS aurantifoha Swingle) in relation to bud union, stock: scion ratio, canopy volume, vegetative flush distribution, flowering and leaf nutrient uptake pattern on 20 rootstock strains. The lowest stock: scion ratio was in plant raised on Cleopatra mandarin (Coorg and Tirupati). The Troyer citrange (Gonicoppal and Chethalli), Carrizo citrange (Chethalli), C 32 and C 35 cltrange imparted maximum ratio of stock and scion indicating the incogenial bud union, whereas remaining twelve rootstock strains showed smooth bud union and fomed congenial stionic combination with acid lime. Acid lime, Alemow (C. macrophylla) and Rangpur lime (Brazilian), exhibited maximum canopy volume. While lowest canopy was found lU plants on Cleopatra mandarin (Coorg and Tirupati). Although all the rootstocks showed a cyclic flush, mduced ambia (Nov.-Dec.), mrig (June-July) and hasta (September) flush in 1995-96 but it was differed in different stionic combination in 1996Â·97. The maximum accumulation of leaf P(0.2%) on C 32 citrange, K (l.93%)and Ca (7,32%) on Rangpur lime (Brazilian) was observed. Leaf Cu, Mn, Zn and Fe content were recerded maximum of 25.3 ppm,73 8 ppm 23.9 ppm and 259.2 ppm with Cleopatra mandarin (Coorg and Morocco), Schaub rough lemon and Troyer citrange (GonicoppaL) respectively. The variation in uptake of leaf micronutrient was found due to yariation in rootstock strains. The induction of generative flush (spring flowering) of acid lime was observed on almost all the rootstQck strains in 3rd year of planting except C 32 (25%), acid lime seedling and Chethalli strain of Troyer citrange (50%) and Chase rough lemon and Coorg and Gonicoppal strains of Cleopatra mandarin (75%) Â